Development of smallholder dairy systems in the Kenya highlands - Bebe, B.O.; Udo, H.M.J.; Thorpe, W.R. (2002)
Kenya is recognized among developing countries for its success in integrating dairy into smallholder farming systems, particularly in the highland areas. The major determinants of this success were colonial history, its favourable agroecology and supportive agricultural policies, and the importance of milk in rural and urban diets. In response to agricultural policies, market opportunities and human population pressure on land, smallholders have changed their farming systems by introducing the Friesian and Ayrshire breeds, keeping smaller herds with fewer heifers but more cows, increasing stocking rates through stall feeding, growing fodder, purchasing feeds and becoming more dependent on external inputs and services. As a result, they can sell more milk. This increasing intensification, here defined as the use of external inputs and services to increase the output quantity and value per unit input, has ensured that more people are maintained per unit of land through increased returns per ha of family land. Because the level of intensfication varies with the agroecological potential for cropping and dairying and with the level of milk market access and household resources, recommendations for production practices supporting intensification will be site-specific. Identifying appropriate recommendations will require a thorough understanding of farmers' objectives for keeping cattle